The perceptions of teachers on the problems of the teaching in Islamic kindergartens : acase study of selected kindergartens in Southern Thailand - Langputeh, Suwannee (Kulliyyah of Islamic Revealed Knowledge and Human Science, International Islamic University Malaysia, 1999)
This study investigates the perceptions of teachers on the problems of teachng in Islamic kindergartens with respect to language, administration and supervision, curriculum, teachers, and evaluation. It also identifies the discernible patterns in the tachers' responses with regard to their age, educational qualifications and teaching experience while their gender factgor is determined to be constance since all respondents in the selected kindergartens were female teachers. The populationof this study conbsisted of 51 female teacheers of Islamic kindergartens in Southern Thailand. The instrument employed for collecting data is a close-ended written questionnaire developed by the researcher herself which comprised of 25 items of problems of teaching. The data are analyzed using descriptive statistcs especially percentages and frequency counts. In addition, the Cronbach formula is used to measure the reliability of the instrument. The study found that there are agreements among the respondents on the problems of language, administration and supervision, curriculum, teachers, and evaluation. There are also discernible patterns in teachers' responses with regard to their age, educational background, and teaching experience. The study concludes with some recommendations for practical guidance and further research.